Obesity prevalence in a cohort of women in early pregnancy from a neighbourhood perspective - Alricsson Marie; Arnoldsson Göran; Sellström Eva; Hjern Anders (BMC, 2009)
Abstract Background The evidence of an association between neighbourhood deprivation and overweight is established for different populations. However no previous studies on neighbourhood variations in obesity in pregnant women were found. In this study we aimed to determine whether obesity during early pregnancy varied by neighbourhood economic status. Methods A register based study on 94,323 primiparous pregnant women in 586 Swedish neighbourhoods during the years 19922001. Multilevel technique was used to regress obesity prevalence on socioeconomic individual-level variables and the neighbourhood economic status. Five hundred and eighty-six neighbourhoods in the three major cities of Sweden, Stockholm, Göteborg and Malmö, during 19922001, were included. The majority of neighbourhoods had a population of 4 00010 000 inhabitants. Results Seven per cent of the variation in obesity prevalence was at the neighbourhood level and the odds of being obese were almost doubled in poor areas. Conclusion Our findings supports a community approach in the prevention of obesity in general and thus also in pregnant women.